Is Individual Metering Socially Sustainable? The Case of Multifamily Housing in France - Bernard Barraqué (Water Alternatives, 2011)
Before generalising water metering and billing at the apartment level for consumer equity reasons, and alleviating the burden of water bills for poor families through increasing block tariffs (IBTs), Paris Council asked for some expert advice. The pros and cons of two separate issues – IBTs efficiency and justice; and individual household metering – were mixed. Our research first summarises various studies of the redistributive effects of tariff changes, first from flat rates to metering, and then from uniform prices to IBTs. We address the particular case of multifamily housing, where it is possible to retain collective billing, while relying on sub-metering to allocate the bill. The limitations of classical econometric surveys on large samples (in terms of understanding households’ strategies with tap water) support the need for supplementary detailed sociological surveys at neighbourhood or building levels, if only to check the unexpected redistributive effects of tariff changes in practice. We review the specific French situation, peculiarly in Paris, to show that individual apartment billing is more costly and tends to have regressive effects. Like other cities in France, Paris abandoned the implementation of Art. 93 of the 2000 law, which encouraged individual billing; and we explain why.